Possible ways to increase the efficiency of the institution of power lustration in Ukraine (Law and Safety, 2020)
It has been emphasized that lustration (purification of power) was once chosen as one of the main mechanisms for resetting all branches of power in Ukraine. The national legislation, which is the legal basis for the functioning of the mechanisms for the purification of power in Ukraine, has been analyzed. It has been clarified that the domestic mechanism of government lustration is ineffective, since in many cases it harmed the interests of the state and society in general. It has been stated that the majority of the ruling elite was never lustrated, and those who were under lustration processes were renewed in their positions as a result of court decisions. The result of such renewals was material compensation (sometimes several dozens or even hundreds of thousands of hryvnias) for the period of so-called forced absence. The decision of the European Court of Human Rights on the Ukraine’s violation of the Convention for the Protection of Human Rights and Fundamental Freedoms dated from November 4, 1950 within the application of mechanisms of power lustration has been studied. The author has emphasized the need for increasing the efficiency and developing mechanisms of power lustration existing for a long period of time. It has been noted that the state is showing excessive activity in the formation and implementation of mechanisms for the purification of power, aimed not at eliminating existing shortcomings, but at expanding the list of persons subject to lustration. Such approaches to the purification of power, being ineffective, contradict a number of standards recognized by the world community. Ways to increase the efficiency of the institution of power lustration in Ukraine have been determined. It has been argued that it is expedient to use such mechanisms of purification of power that have a personalized addressee. It has been noted that establishing the guilt of a particular official in committing an offense in the field of his professional activity may result in his removal from office and a ban on holding this position in the future. It has been established that all the standards of purification of power will be observed in this case: the guilt will be personal, an individual objective investigation will be carried out, and the person will be able to use all the mechanisms to protect own rights.
Keywords: lustration of power in Ukraine; lustration; ways to increase; mechanism of power lustration; legal principles; decisions of the European Court of Human Rights